Social innovation in sustainable tourism as a proposal for economic reactivation in the post-pandemic - Vargas Prieto, Amanda; Lafosse, Hadrien; Morales, Carlos (Cooperativismo & Desarrollo, 2023)
Given the potential of tourism in Colombia, together with the necessity to make it more adaptable, inclusive, and sustainable before the crisis, it is necessary to bring forward a new conceptualization prioritizing alternative environmental and sociocultural values. The purpose of this paper is to develop a theoretical framework presenting the relationship between sustainable tourism and social innovation, and to make recommendations to reach sustainable development in this sector in Colombia. Using the content analysis technique, a literature review is carried out on sustainable tourism and social innovation to identify some fundamental criteria for the creation of social innovation in tourism activities. Finally, a social innovation strategy for sustainable tourism in Colombia is put forward. Such strategy is rooted in the following five criteria: embeddedness, multifunctionality, public goods and shared resources, niche and institutional markets, and governance.